Primary health care with the participation of the local government level articulated to the budgeted maternal and neonatal health program - Vargas-Zafra, Lupe Antonieta (2024)
Objective: Describe the effectiveness of primary maternal health care through the budget program 0002 Maternal Neonatal Health, with the participation of the local government level. Material and methods: The programming and budget execution of the activity was analyzed: Municipal actions that promote sexual and reproductive health with emphasis on healthy motherhood. To evaluate the effectiveness, result indicators of the budget program were considered that are linked to the functions of the local government level within the framework of the Organic Law of Municipalities. Results: It was found that only 20 departments have a programmed budget aimed at strengthening primary health care in maternal health care; Of these, budget programming is inconsistent in 80% of local governments, execution is 75.3% on average in the last five years. The departments that have the highest cases of maternal death in the last two years are Piura, la Libertad, Lambayeque and Cajamarca; Of them, only Cajamarca has more than 10 maternal waiting houses. Pregnancy in adolescents aged 15 to 19 has increased by 1.3% in 2022 compared to 2021; A total of 31 cases of maternal death in adolescents have been recorded. Conclusions: The budget assigned to the local government level is insufficient, inconsistent and inefficient, which limits it from fulfilling its role as manager of primary health care in its jurisdictional areas.